Pyrolysis and combustion of pulp mill lime sludge - Magalhaes, W. L. E.; Job, Aldo Eloizo [UNESP]; Ferreira, C. A.; da Silva, H. D. (Elsevier B.V., 2008)
Thermal degradation and gaseous products evolving from pyrolysis and combustion of pulp mill lime sludge were investigated using Thermogravimetric Analysis in conjunction with Fourier Transform Infrared Analysis (TG-FTIR). The materials were studied in temperatures ranging from 25 to 1000 degrees C. The addition of calcium carbonate caused a decrease in S-containing compounds that evolved from the sludge combustion. The temperature range for decomposition by pyrolysis is higher than for decomposition by combustion. FTIR spectra of the gases evolved show considerable amounts of CO(2), in addition to HNCO and CH(4) absorptions. NH(3) gas was not detected, and sulfur and nitrogen-containing gases only developed in insignificant amounts. The sludge combustion presents two maxima pattern, determined by the CO(2) and H(2)O evolution, that could be associated to the flaming of volatile matter - for the first maximum followed by a glowing of the fixed carbon - for the second maximum. Results show that pulp mill lime sludge can be used as an alternative energy source if pollutant gases and heat expended from dewatering are carefully managed. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: thermal decomposition; combustion; pyrolysis; pulp sludge analysis; TG/FTIR